2015
DOI: 10.1111/neup.12231
|View full text |Cite
|
Sign up to set email alerts
|

Atypical teratoid/ rhabdoid tumor, an immunohistochemical study of potential diagnostic and prognostic markers

Abstract: Atypical teratoid/rhabdoid tumor (AT/RT) is a rare tumor of the CNS mostly seen in infants and is often associated with a dismal outcome. Despite the heterogeneous morphology and/or immunoprofile, its diagnosis nowadays relies on the negative INI-1/BAF47 nuclear immunostain in tumor cells. We aim to investigate a number of immunohistochemical antibodies as potential diagnostic and prognostic markers. All AT/RT cases in patients younger than 18 years of age were included. Demographics, clinical features and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
2
9
1
Order By: Relevance
“…1,22 In 2 different studies by Al-Hussaini et al, necrosis has been reported in 100% cases while calcification has been noted in 20% to 26% cases. 21,23 However, in the present series, necrosis was observed in 62% cases; while calcification, considered as a radiological soft clue for diagnosing AT/RT, 24 was seen in only 13% cases. Nevertheless, the discordance in the frequency for these parameters can be explained by the disparity in the sample size and with sampling bias.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…1,22 In 2 different studies by Al-Hussaini et al, necrosis has been reported in 100% cases while calcification has been noted in 20% to 26% cases. 21,23 However, in the present series, necrosis was observed in 62% cases; while calcification, considered as a radiological soft clue for diagnosing AT/RT, 24 was seen in only 13% cases. Nevertheless, the discordance in the frequency for these parameters can be explained by the disparity in the sample size and with sampling bias.…”
Section: Discussioncontrasting
confidence: 67%
“…Results for expression of the epithelial and myogenic immunohistochemical markers were comparable with the series of Al-Hussaini et al 21 The IHC results for synaptophysin and GFAP were comparable too with that described in the literature. 23,27 Similar to histological divergence, immunohistochemical divergence as noted in this study is a known feature of AT/RT, which formed the basis of diagnosis before the advance and availability of IHC for INI1 protein. 3 p53 protein overexpression has been associated with poor prognosis in medulloblastoma/primitive neuroectodermal tumor 28,29 ; however, akin to this study, similar prognostic value have not been ascertained in AT/RT.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Immunohistochemistry also has potential for predicting prognosis, with one study showing association of FLI-1 and cyclin D1 immunopositivity with improved survival. 40 …”
Section: Histopathologymentioning
confidence: 99%
“…WT-1 genes, PLI-1 and cyclin D1 are potential prognostic markers. (13) Interesting observation of Cerebellar Mutism Syndrome (CMS) was observed following surgery of posterior fossa tumours in children. Mutism is prominent and strokes, infections and ataxia being less common.…”
Section: Discussionmentioning
confidence: 99%